Pengembangan Aplikasi Manajemen Tata Kelola Perusahaan Berbasis Mobile - Tri Jaka Satria; Rr Hajar Puji Sejati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The digitalization of corporate governance has become an essential need for improving the effectiveness and accuracy of human resource management. Many companies still rely on manual methods for recording attendance, leave applications, and payroll calculation, which are prone to administrative errors and lack accountability. This research aims to develop a mobile-based corporate governance application capable of integrating various administrative processes into a centralized system. The application offers several key features, namely employee data management, photo-based check-in and check-out attendance, digital leave applications, and an automated payroll mechanism. The attendance system is equipped with location validation to ensure employees are within a ± 30 meter radius of the designated office point, while tardiness is automatically recorded and subjected to a salary deduction of Rp2,000 for every 5 minutes, in accordance with company-established regulations. All data is synchronized in real-time, supporting transparency and expediting administrative processes. The test results show that the application is capable of enhancing operational efficiency, reducing the potential for fraud, and strengthening the principles of transparency and accountability in corporate governance. By integrating several critical processes within a single mobile platform, this system proves to be effective in assisting companies to implement a more modern and measurable governance framework.